Repositioning of the Angiotensin II Receptor Antagonist Candesartan as an Anti-Inflammatory Agent With NLRP3 Inflammasome Inhibitory Activity - Lin, Wen-Yu; Li, Lan-Hui; Hsiao, Ya-Yun; Wong, Wei-Ting; Chiu, Hsiao-Wen; Hsu, Hsien-Ta; Peng, Yi-Jen; Ho, Chen-Lung; Chernikov, Oleg V.; Cheng, Shu-Meng; Yang, Shih-Ping; Hua, Kuo-Feng (Frontiers in Immunology, 2022)
Aberrant activation of the NLRP3 inflammasome promotes the pathogenesis of many inflammatory diseases. The development of the NLRP3 inflammasome inhibitors from existing drugs for new therapeutic purposes is becoming more important. Candesartan is an angiotensin II receptor antagonist widely used as a blood pressure-lowering drug; however, the inhibitory potential of candesartan on the NLRP3 inflammasome has not yet been investigated. We demonstrated that candesartan significantly inhibited the NLRP3 inflammasome and pyroptosis in macrophages. Mechanistic analysis revealed that candesartan inhibited the expression of NLRP3 and proIL-1β by suppressing NF-κB activation and reducing the phosphorylation of ERK1/2 and JNK1/2. Candesartan reduced mitochondrial damage and inhibited the NLRP3 inflammasome assembly by suppressing NLRP3 binding to PKR, NEK7 and ASC. In addition, candesartan inhibited IL-1β secretion partially through autophagy induction. Furthermore, oral administration of candesartan reduced peritoneal neutrophil influx, NLRP3 and ASC expression in peritoneal cells, and lavage fluid concentrations of active caspase-1, IL-1β, IL-6 and MCP-1 in uric acid crystal-injected mice. These results indicated that candesartan has board anti-inflammatory effects and has the potential to be repositioned to ameliorate inflammatory diseases or NLRP3-associated complications.